Husband’s Abandonment of his Own Rights and Joint Rights and its Criteria in Issues of Personal Status: Examples on Juristic Studies Compared with Jordanian Personal Status Law of the Year 2019 - Almaghayreh , Nabeel (Dirasat: Shari’a and Law Sciences, 2020)
This research investigates the issue of abandonment and its criteria in issues of personal status, in particular those related to husband’s rights and joint rights. It aims at clarifying the concept of abandonment, its kinds, criteria, and application in Jordanian personal status law. This is in addition to its curative and practical role of such legal rulings. This is done by studying juristic examples from the personal status law. The study shows that there is more than one form of abandonment and the curative and practical role played by jurisprudence of abandonment in issues of personal status. The study recommends judges to take into consideration the rulings of abandonment related to husband’s rights and joint rights and the criteria mentioned in the research when judicial procedures are applied, in addition to the achievement of legal objective and the interest of those who have the right of abandonment.